Gastrointestinal Involvement in Lipoid Proteinosis: A Ten-Year Follow-Up of a Brazilian Female Patient - Juliana Custódio Lima; Cristiane Kibune Nagasako; Ciro Garcia Montes; Irene Harumi Kamata Barcelos; Rita Barbosa de Carvalho; Maria Aparecida Mesquita (Case Reports in Medicine)
Lipoid proteinosis is a rare autosomal recessive disease characterized by the deposition of hyaline material in the skin and internal organs. The main clinical features are hoarseness and typical skin lesions. In this report we describe the endoscopic and radiologic findings in a Brazilian female patient presenting extensive gastrointestinal involvement and the evolution of the detected lesions in ten years of follow-up. Initial upper endoscopy and colonoscopy showed a similar pattern of multiple yellowish nodules throughout the esophagus, stomach, duodenum, and colons. Histological analysis confirmed the diagnosis of lipoid proteinosis. In addition, small bowel follow through demonstrated numerous well defined, round, small filling defects throughout the jejunum. Ten years later, the esophageal lesions remained the same, but none of the previous alterations were detected in the stomach, duodenum, and colons. In conclusion, lipoid proteinosis may affect all gastrointestinal organs with the same pattern of macroscopic and microscopic lesions. Some lesions may regress with increasing age.